SEJARAH KEHIDUPAN MASYARAKAT SUKU BONAI DESA BABUSSALAM ROKAN KECAMATAN PUJUD KABUPATEN ROKAN HILIR - Putri, Guswita; Isjoni, Isjoni; Melay, Ridwan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Bonai tribe is one of the isolated tribes in Riau that lives on the banks of the Rokan River. This Bonai tribe spreads in several regions such as Left Rokan and Rokan Kanan. The Bonai Tribe is one of the KAT communities in Riau which is a marginal community that is marginalized in all aspects of its life. The KAT community in Indonesia is spatially or geographically located far from the centers of progress and development that exist. A community becomes alienated due to several factors including geographical distance, social interaction, science and technology, education. According to the Bonai Tribe, the word "Bonai" comes from the word "Manai" where in the language of the Bonai the word Manai means lazy. this is related to the habits of the Bonai people who are known for their lazy people. The Bonai tribe was brought by two sisters who migrated to Brunei, namely Sutan Harimau and Sutan Janggut. Not unlike other KAT communities, the Bonai people also live behind. The Bonai Tribe makes a living as fishermen, farming and expecting forest products. The Bonai Tribe is rich in culture and tradition. One of the well-known traditions of the Bonai Tribe is the Buong Kwayang or Bodeo Dance which is a traditional dance of the Bonai Tribe which is still believed by the Bonai Tribe to this day. The purpose of this study was to find out the history of the origin of the Bonai Tribe, to find out the social conditions, to find out the culture of the Bonai Tribe, to find out how far the government's attention to the Bonai Tribe was. The method used in conducting this research is the historical method in which the steps are heuristics, verification, interpretation and historiography. Data collection techniques used are observation techniques, interview techniques, documentation techniques and literature study techniques.Key words: History, Life, Society, Bonai Tribe